Chemical Composition, Antioxidant and Antimicrobial Activities of the Essential Oils of Three Algerian Lamiaceae Species - Yousfi, Mohamed; Benabed, Khadidja Houda; Gourine, Nadhir; Ouinten, Mohamed; Bombarda, Isabelle (Current Nutrition & Food Science, 2017)
Background: The present work investigates the chemical composition, the antioxidant and the antimicrobial activities of the Essential Oils (EOs) of three species of the Lamiaceae family gowning in Algeria: Thymus vulgaris L., Thymus algeriensis Boiss. & Reut. and Mentha pulegium L. Methods: Essential Oils (EOs) obtained by hydrodistillation of the aerial parts of the studied plants were analyzed by GC and GC-MS. The antioxidant activity of the EOs was determined using two different assays: free radical scavenging activity of DPPH• (2,2-diphenyl-1-picrylhydrazyl) and Phosphomolybdenum reducing power. The EOs were also tested for their antibacterial and antifungal activities against eight pathogenic bacteria (Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella typhi, Escherichia coli, Bacillus cereus, Staphylococcus aureus, Methicillin resistant strain of S. aureus “MRSA” and Enterococcus faecalis); a yeast (Candida albicans); and a fungi (Fusarium oxysporum). Results: For DPPH assay, T. vulgaris presented very interesting activity. At the opposite, T. algeriensis (Aflou) and M. pulegium, were the most active EOs in term of Phosphomolybdenum assay. The antimicrobial activity of T. vulgaris was found to be the most active EO and exhibited important resistance against most of studied bacteria. For disc diffusion test, the most active EO plant was T. algeriensis. Alternatively, and for antifungal activity, T. vulgaris presented the highest value of MFC. Conclusion: The antioxidant activity test’s results showed that the EOs exhibited important reducing powers but weak scavenging activities. On the other hand, it was found that some EO samples have shown very interesting antimicrobial activities. Actually, among the investigated EOs, T. vulgaris presented the strongest antibacterial and antifungal activities.
Keywords: Thymus vulgaris L; Thymus algeriensis Boiss; & Reut; Mentha pulegium L; DPPH assay; phosphomolybdenum assay, antimicrobial activity; essential oil.